Proceedings of the 7th International Conference on Human Computer Interaction With Mobile Devices &Amp; Services 2005
DOI: 10.1145/1085777.1085831
|View full text |Cite
|
Sign up to set email alerts
|

GpsTunes

Abstract: We combine the functionality of a mobile Global Positioning System (GPS) with that of an MP3 player, implemented on a PocketPC, to produce a handheld system capable of guiding a user to their desired target location via continuously adapted music feedback. We illustrate how the approach to presentation of the audio display can benefit from insights from control theory, such as predictive 'browsing' elements to the display, and the appropriate representation of uncertainty or ambiguity in the display. The proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This system guides the user to a pre-defined location using song volume panning to indicate bearing to the target and general volume level adjustment to indicate the distance to the target. The reported user behavior from user tests in [11] is similar to our observations from user tests with PING! application.…”
Section: Related Worksupporting
confidence: 81%
See 1 more Smart Citation
“…This system guides the user to a pre-defined location using song volume panning to indicate bearing to the target and general volume level adjustment to indicate the distance to the target. The reported user behavior from user tests in [11] is similar to our observations from user tests with PING! application.…”
Section: Related Worksupporting
confidence: 81%
“…The gpsTunes prototype [11] combines an mp3 player implemented on a PocketPC with an external navigation module. This system guides the user to a pre-defined location using song volume panning to indicate bearing to the target and general volume level adjustment to indicate the distance to the target.…”
Section: Related Workmentioning
confidence: 99%
“…Work on music based guidance includes gpsTunes [8], where initial testing of a prototypical system had shown that it was possible to allow users to navigate in the real world, using a combined Audio/GPS player to aid navigation. Similarly Etter et al [1] describe, Melodious Walkabout, which again utilises a users music to guide them to their desired location.…”
Section: Location-aware Audiomentioning
confidence: 99%
“…As an example application of our density probing system we developed a trajectory following application which follows naturally from the gpsTunes system described in [8,10]. It is designed to guide a user along a desired trajectory using audio and vibrotactile feedback via their mobile device, be that a PDA, music player or mobile phone.…”
Section: Trajectory-tunesmentioning
confidence: 99%
“…Portable devices such as smart phones and portable music players have also come to be used as methods of navigation [1] [2]. Since such cues are provided indirectly, they require processes: the pedestrian can behave appropriately on the basis of a cue only after the cue is obtained and its meaning interpreted.…”
Section: Introductionmentioning
confidence: 99%